Tartrate resistant acid phosphatase positive splenic lymphoma: a relatively benign condition occurring in a time-space cluster?. Issue 9 (September 1990) - Kettle, P; Morris, T C; Markey, G M; Alexander, H D; Curry, R C; Hayes, D; Cameron, C H; Toner, P G
Abstract : Conventional light and electron microscopic studies, together with cytochemical and immunocytochemical staining procedures, were carried out to ascertain whether the lymphomata of four elderly female patients living within 10 kilometers of each other, who presented within a short space of time with massive splenomegaly and varying cytopenia, belonged to any particular subgroup of lymphoma. In each case the lymphoma had a diffuse pattern and mature B cell phenotype. The malignant cells were of uniform cell type, slightly larger than admixed polymorphonuclear leucocytes, and showed minimal nuclear irregularity and positivity for tartrate resistant acid phosphatase (TRAP) staining. Their clinical and morphological features were compared with those of other lymphoproliferative disorders, but while sharing some features in common with each condition, this small group of patients seemed to have a unique combination of findings. The cytopenias of all four responded well after removal of the spleen and their disease has not been aggressive. It is concluded that these patients have a distinct subgroup of lymphoma, which it is important to recognise so that inappropriate use of aggressive cytotoxic drugs can be avoided.